Metabolite Profiling And Dna Barcoding Analysis Of 35 Malaysian Medicinal Plants - Lai, Mei Wei (2022)
Medicinal plants have been used in traditional medicine all over the world. Today, Malaysian medicinal plant species are rarely documented in scientific literature. The purpose of this research was to collect 35 selected medicinal plants, prepared herbarium voucher, the supplement scientific information, complete DNA barcode and metabolite profile analysis of selected local medicinal plants. Medicinal plants must be identified correctly to be effective as medicine. Unrelated species can lead to impaired downstream experiments. Morphology approach is still at the forefront of measuring plant identity because the starting material is important to avoid undesirable results. The 35 medicinal plants were collected from Selangor, Negeri Sembilan and Johor. Three barcode regions including ribulose 1,5-biphosphate carboxylase (rbcL), maturase K (matK), and internal transcribed spacer (ITS) were tested for their DNA ic software and databases were utilized to retrieve the information of LC-MS/MS experiment. The 35 species were successfully collected and macroscopic photographs of 35 species were recorded. Plant identification confirmed by taxonomist. Dried specimen was mounted on herbarium paper with herbarium label. Herbarium vouchers were deposited at Perdana Botanical Garden Kuala Lumpur, Malaysia. BLAST result of matK successfully matched 52.4% of the queries against the reference database, tentatively proposed the identification rate of matK was higher compared to rbcL (34.3%) and ITS (35.8%). Three single loci were not likely to provide 100% species identification because it is impossible to use a single barcode fixed to all plant taxa. There were 44 N-containing compounds, 142 Phenolics, 87 Terpenes, the 35 medicinal plants. Majority of the putative compounds were known as confirmed the proper scientific names of 35 local medicinal plants and provided the herbarium vouchers, DNA barcoding and putative compounds to achieve mutual benefit for present and future generations.